Real-time PCR melting analysis with fiber optic SPR enables multiplex DNA identification of bacteria. Issue 6 (16th February 2016) - Daems, D.; Knez, K.; Delport, F.; Spasic, D.; Lammertyn, J.
Abstract : A fiber optic surface plasmon resonance (FO-SPR) technology was developed that enables simultaneous quantification and identification of multiple DNA targets on the same platform. Abstract : A fiber optic surface plasmon resonance (FO-SPR) technology was developed that enables simultaneous quantification and identification of multiple DNA targets on the same platform. The bioassay was based on the hybridization/melting of DNA-coated Au nanoparticles on the FO-SPR sensor when targets are present. The multiplex concept was successfully demonstrated on two related bacteria and for detection of multiple mutations in sequences. In conclusion, FO-SPR technology shows a great potential as a next generation in vitro diagnostics tool.